Freedom on the Free Place, Alaska, as Seen in Into The Wild by Jon Krakauer - Lusia Melina Manik (STBA Prayoga Padang, 2015)
Into the Wild is a novel written by Jon Krakauer. The novel tells the story about a man, John McCandless, who wants to be free from all the things that he does not like. The story begins when he escapes from his daily life and lived in the free place, Alaska. He wants to live in Alaska in order to get his real freedom where he can do many things that he likes. This study analyzed the reason why the main character, John, wants to escape. To analyze the novel, intrinsic and extrinsic approaches were used. Objective theory was used because the writer analyzed the aspect of literary work itself. To support the analysis, a psycology approach was used by using the behaviorist theory. The findings indicated that there were several reasons that stimulated Chris to escape and disappear from his daily life. They were anger, love, and infatuated.